Precise Control Light Emission of PVDF-CH3NH3PbBr3-xClx Nanocrystalline Films Using a Cl-(CH3OH)n System - Wang, Rui (Langmuir : the ACS journal of surfaces and colloids, 2024)
Methylammonium lead halide perovskites with highly efficient pure-color or white-light generation have gained increasing scientific interest and promote the development of a great commercial opportunity in displays, lighting, and other applications. However, the poor stabilities, lead toxicity, and unfriendly solvents and ligands in the growth process severely restrict their commercial application. Here, we proposed a green method for preparing uniform and stable polymer-encapsulated photoluminescence (PL) tunable CH3NH3PbBr3-xClx NC thin films at room temperature. Utilizing the swelling effect between alcohol compounds and organic polymers and the ionization of NaCl in methanol solution, the anion exchange process can be achieved rapidly within 7 min. Moreover, the PL wavelengths of the CH3NH3PbBr3-xClx NCs films were precisely tuned with steps as fine as 2 nm. Experimental results showed that NaCl dissolved in methanol solution can form Cl-(CH3OH)n, which brings ionized Cl into the polymer-encapsulated CH3NH3PbBr3 NCs film for CH3NH3PbBr3-xClx NCs film growth. Based on the swelling and anion exchange dynamics, a modified NaCl-CH3OH-MABr solution system was developed to trigger CH3NH3PbBr3-xClx NCs film PL emission tuning from 528 to 463 nm with several-fold intensity enhancement. The realization of precisely controlled photoluminescence from the perovskite nanocrystal film would have wide applications in the optical and imaging fields